O13.3 High prevalence of cervico-vaginal infections among female adolescents in four urban regions of panama. (14th July 2019) - Gabster, Amanda; Mayaud, Philippe; Martinez, Alexander; Dyamond, José; Pitano, Sherly; Castillero, Omar; Castillo, Jorge; Pascale, Juan
Abstract : Background: Few data exist on cervico-vaginal STI among adolescents in Panama. The aim of this study was to determine the prevalence and correlates of cervico-vaginal STIs among female school-going adolescents in urban regions of Panama. Methods: A multicentric cross sectional study using multistage cluster sampling, with random selection of schools and clusters was conducted among participants aged 14–19 years enrolled in public high schools in the urban regions of Panama, San Miguelito, Colón, and Panamá Oeste, accounting for 53% of the country´s population. One region was studied each year between 2015 and 2018. Participants self-administered a questionnaire and gave urine samples. Those who self-reported sexual activity were tested for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium (MG), and Trichomonas vaginalis (TV)by PCR. Correlates of infection were analyzed using univariate (OR) and age adjusted analyses (AOR). Results: A total of 1404 female adolescents (median age 17) participated. More than half (57.3%) reported a history of sexual activity; of those, 27.4% had ≥1 positive STI test (22.8% positive for CT, 2.2%NG, 3.9%MG, 2.3%TV). Almost all participants with NG also had CT (15/18, 88.2%); nearly half with MG also had CT (13/31, 41.9%). Correlates did not change when removing non-CT infections; correlates of one or more STI included: three or more sex partners in the past year (AOR=4.12, 95%CI: 1.13–15.1), sex with a casual partner at least once (AOR=3.5, 95%CI: 1.6–7.7), reported sex in the past month (OR=1.8, 95%CI: 1.3–2.7), and reported anal sex (OR=1.6, 95%CI: 1.1–2.4). Protective correlates included study sites Colón and Panamá Oeste (AOR=0.3, 95%CI: 0.1–0.7; AOR=0.2, 95%CI 0.1–0.4). Conclusion: This study found very high prevalence of cervico-vaginal STIs, especially CT among high school-going female adolescents in urban Panama regions. Results indicate the need for interventions that target female adolescents, such as screening and treatment in urban Panama. Disclosure: No significant relationships.